DDDR-22. TRANSLATION OF THE PDGFRA/KIT INHIBITOR AVAPRITINIB FOR PEDIATRIC HIGH-GRADE GLIOMA. (14th November 2022) - Mayr, Lisa; Trissal, Maria; Schwark, Kallen; Labelle, Jenna; Kong, Seongbae; Groves, Andrew; Supko, Jeffrey; Hack, Olivia; Marques, Joana; Panditharatna, Eshini; Dubois, Frank; Greenwald, Noah; et al.
Abstract: Pediatric high-grade glioma (pHGG) is an incurable disease with a median survival of less than 6 months post-progression and no effective targeted therapy. PDGFRA is commonly altered in pHGG, but targeting PDGFRA in this disease has been unsuccessful, likely due to poor central nervous system (CNS) penetrance. Avapritinib is a novel and CNS-penetrant PDGFRA/KIT inhibitor that is FDA-approved for adults with unresectable or metastatic PDGFRA exon 18-mutant gastrointestinal stromal tumor (GIST) and is being studied in CNS tumors. We performed a pre-clinical and clinical assessment to determine the potential suitability of avapritinib therapy in PDGFRA-driven glioma. A multi-institutional cohort genetic analysis revealed PDGFRA amplification and mutation in 10.2% and 6.1% of pHGG, respectively. Additionally, PDGFRA expression in the absence of genetic events was significantly increased in H3K27-altered diffuse midline glioma (DMG) compared to H3-wildtype pHGG. Avapritinib performed well in: (i) mutant PDGFRA enzyme inhibition and wildtype inhibition at high dose, (ii) minimal off-target kinase inhibition, (iii) brain penetration (peak 10 µM), and (iv) proliferation/pPDGFRA reduction in PDGFRA -amplified and mutant pHGG cell lines. Avapritinib treatment in an aggressive PDX model of pHGG resulted in significant survival benefit. We pursued treatment of eight pediatric and young adult HGG patients with avapritinib across seven institutions. Patients were a mixture of local (N = 4) and metastatic disease (N = 4); all patients were post-initial radiation, with 7/8 having progressed on prior treatment. 7/8 patients had PDGFRA amplifications or mutations, and 7/8 had H3K27M mutations. Therapy was generally well-tolerated. 4/8 patients showed radiographic response to avapritinib, with one patient demonstrating complete response of target lesion and remains on therapy. Avapritinib levels in patients' CSF and brain tumor tissue reached micromolar levels. These results demonstrate that avapritinib is a potent, selective, and CNS-penetrant PDGFRA/KIT inhibitor that is promising for further study in pHGG with relevant alterations.